Whole genome sequence-based characterization of virulence and antimicrobial resistance gene profiles of Staphylococcus aureus isolated from food poisoning incidents in eastern China - Yu, Shuyang; Zhou, Yuxuan; Feng, Dan; Jiang, Quangui; Li, Tianle; Jiang, Guilai; Zhou, Zhemin; Li, Heng (Frontiers in Microbiology, 2023)
Staphylococcus aureus is an opportunistic foodborne pathogen occasionally isolated from diarrhea patients. In recent years, increasing studies have reported the detection of S. aureus in food poisoning incidents due to food contamination in the North and South of China. However, the epidemiology and genetic characteristics of S. aureus from food poisoning incidents in Eastern China remain unknown. The present study examined the genetic characteristics, antimicrobial resistance, and virulent factors of multidrug-resistant S. aureus isolated from 22 food poisoning incidents reported by the hospitals and health centers in Eastern China from 2011 to 2021. A total of 117 resistant and enterotoxigenic S. aureus isolates were collected and sequenced, among which 20 isolates were identified as methicillin resistant. Genetic analysis revealed 19 distinct CC/ST types, with CC6, CC22, CC59, CC88, and CC398 being the most frequent variants in methicillin-resistant S. aureus (MRSA). A considerable shift in CC types from CC1 to CC398 between 2011 and 2021 was observed in this study, indicating that CC398 may be the main epidemic strain circulating in the current food poisoning incidents. Additionally, genes for enterotoxins were detected in 55 isolates, with a prevalence of 27.8% (27/97) for methicillin-sensitive variants and 35.0% (7/20) for MRSA. The scn gene was detected in 59.0% of the isolates, demonstrating diverse contaminations of S. aureus among livestock-to-human transmission. Of the 117 isolates, only ten isolates displayed multi-drug resistance (MDR) to penicillin, tetracycline, and macrolides. None of the 117 foodborne S. aureus isolates tested positive for vanA in this study. Together, the present study provided phylogenetic characteristics of S. aureus from food poisoning incidents that emerged in Eastern China from 2011 to 2021. Our results suggested that these diarrhea episodes were hypotonic and merely transient low-MDR infections, however, further research for continued surveillance given the detection of virulence and antimicrobial resistance determinants is required to elucidate the genomic characteristics of pathogenic S. aureus in food poisoning incidents in the context of public health.